The Importance of Critical Thinking in Teaching Foreign Languages (Open Academia: Journal of Scholarly Research, 2023)
In this article, the importance of critical thinking in teaching foreign languages, one of the new technologies is the formation of critical thinking skills in students , that many different factors can affect students' critical thinking skills, critical thinking is taught and learned information is given that it is a process.